Hybrid Lightwave/RF Connectivity for 6G Wireless Networks - Papanikolaou, Vasilis K.; Diamantoulakis, Panagiotis D.; Karagiannidis, George K. (6G Mobile Wireless Networks, 2021)
The integration of lightwave technology in wireless access has been groomed, due to its clear superiority in various aspects of wireless networking. Despite its many advantages, though, its very nature renders it a dependent technology, to be used complimentary with conventional RF networks. Therefore, the notion of hybrid lightwave/RF networking was established as a promising solution to bring the best of both worlds. The synergy between the two networks can offer significant gains in spectral efficiency and network densification, since optical networks can deliver much higher data rates per area. However, because of the heterogeneous networking, several challenges arise, as such hybrid lightwave/RF networks have been studied for resource allocation, user scheduling and integration with other promising technologies of the next generations of wireless access, such as non-ortogonal multiple access (NOMA). Apart from that, the simultaneous lightwave information and power transfer (SLIPT) has also attracted the interest of academia and industry alike as a means for more energy sustainable networks. In this chapter, the challenges of hybrid lightwave/RF networking are detailed and the interplay between hybrid lightwave/RF networks and enabling technologies of the next generations of wireless access is discussed. Finally, the concept of cross-band network design is presented as an enabling technology for the sixth generation of wireless networks (6G